Orientasi Baru dalam Pedagogik: Transformasi Paradigma Pendidikan Abad ke-21 - Alfiani Nur Julia; Rugaiyah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The transformation of pedagogical paradigms is a response to the changing times, marked by technological advancements, the demand for 21st-century competencies, and an increasing awareness of the need for more humanistic learning approaches. This study aims to examine the new orientations in pedagogy through a systematic review of 30 national and international scholarly journals published over a ten-year period (2015–2025). The Systematic Literature Review (SLR) method is employed to identify key themes such as the shifting role of teachers, technology integration, authentic assessment, project-based learning, and character development. The findings indicate that contemporary pedagogy requires a comprehensive transformation in curriculum design, learning strategies, and assessment systems. Furthermore, learning must be contextualized to remain relevant to both local and global needs, while fostering the development of reflective, adaptive, and competitive students. Thus, the new orientation in pedagogy addresses not only the technical aspects of instruction but also reflects a transformative, inclusive, and sustainable vision of education.